The Development of Confidence in English Speaking Using Role Playing Method - Kongsamruay, Kampheeraphap (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The objectives of this research were to study and compare the confidence of English speaking by using the Role-Playing method before and after of the first year students in Bachelor of Arts (English). The population were 13 students in Bachelor  of Arts (English) at Mahamakut Buddhist University Isan Campus and the researcher applied experimental research in a group pretest-posttest to find the confidence of English speaking. The researchers used the questionnaires to collect the data from 13 students and 3 teachers and analyzed by mean, standard deviation and t-test dependent statistics. The results were as follows: 1. The students’ posttest was higher than pretest. The mean scores on English speaking in pretest were 2.53 and posttest were 4.42 and the mean scores on English speaking from three teachers in pretest were 2.62 and posttest were 4.44. After  using Role-Playing method, it was found that the highest score was 4.69 in the number 5 “I don’t worry about what my mistake to speak”. The second was 4.53 in the number 7 and 10 “I’m confident to use the English language.” and “I would like to use the English language to communicate if I have a chance.” In the part of teacher analysis, it was found that the highest was 4.65 in the number 9 “The students don’t avoid to answer the question in the English language.” In comparison between pretest and posttest, it was found that the students had the confidence to speak the English language by applying Role-Playing method with the statistical significance at the 0.05 level. 2. The student’s confidence in English speaking by using Role-Playing method was in the highest level.